2007
DOI: 10.1016/j.cognition.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidentiality in language and cognition

Abstract: What is the relation between language and thought? Specifically, how do linguistic and conceptual representations make contact during language learning? This paper addresses these questions by investigating the acquisition of evidentiality (the linguistic encoding of information source) and its relation to children's evidential reasoning. Previous studies have hypothesized that the acquisition of evidentiality is complicated by the subtleness and abstractness of the underlying concepts; other studies have sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
132
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 74 publications
14
132
0
5
Order By: Relevance
“…For example, Aksu-Koç (1988) found Turkish monolinguals understood the witnessed form (-dI) at about age 4-5, but the unwitnessed form (mIs) only at age six. Similar findings are reported by and Papafrago, Li, Choi and Han (2007) for Korean. Fitneva (2007Fitneva ( , 2008 found Bulgarian monolinguals understood the contrasts at age six, though imperfectly.…”
Section: Acquisition Of Evidentialssupporting
confidence: 80%
“…For example, Aksu-Koç (1988) found Turkish monolinguals understood the witnessed form (-dI) at about age 4-5, but the unwitnessed form (mIs) only at age six. Similar findings are reported by and Papafrago, Li, Choi and Han (2007) for Korean. Fitneva (2007Fitneva ( , 2008 found Bulgarian monolinguals understood the contrasts at age six, though imperfectly.…”
Section: Acquisition Of Evidentialssupporting
confidence: 80%
“…This pattern has been previously noted in the developmental literature (Aksu-Koç, 1988;Ozturk & Papafragou, 2015;Papafragou, Li, Choi, & Han, 2007), but its origins have not been systematically explored. Our goal is to offer new, more robust empirical evidence for the asymmetry focusing on the acquisition of evidential morphology in Turkish; more importantly, we seek to evaluate the relative contribution of methodological demands and the psycholinguistic properties of evidentiality to children's comprehension difficulties.…”
Section: Introductionmentioning
confidence: 81%
“…A further study by Papafragou et al (2007) showed that this asymmetry is not language-specific. In that study, 3-and 4-year-old Korean children were quite successful in producing both a direct (-e) and an indirect/reportative morpheme (-tay); nevertheless, children had difficulty in a ''who-said-it" task measuring evidential comprehension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHILDES). It has grappled with a much broader typological slice of languages and has covered a range of linguistic phenomena that have been barely or not at all yet addressed in adult processing research, for example, evidentiality (Aksu & Slobin, 1986;Fitnever & Matsui, 2009 and papers therein;Papafragou, Li, Choi & Han, 2007), ergativity (Allen, 1996;Bavin, 1992;Bavin & Stoll, 2013;Fortescue & Olsen, 1992;Imidadze & Tuite, 1992;Narasimhan, 2005;Ochs, 1982;Pye, 1990Pye, , 1992Slobin, 1985Slobin, , 1992Van Valin, 1992), and serial verb constructions (Fung, 2011;Lee & Naigles, 2005).…”
Section: A Very Brief History Of Comparative/crosslinguistic Studiesmentioning
confidence: 99%